Species of the Devonian aulacopleurid trilobite Cyphaspides from southeastern Morocco. (January 2020) - Chatterton, Brian D.E.; Gibb, Stacey; McKellar, Ryan C.
Abstract: Three new species of Cyphaspides are proposed: C. ammari, C. nicoleae, and C. pankowskiorum . These species are based on specimens obtained from Middle Devonian (Eifelian) strata of the Bou Tchrafine Group, near Erfoud, in the Province of Errachidia, southeastern Morocco. The present contribution enhances our knowledge of Cyphaspides by providing details of three new species that are based on well-preserved, complete, and articulated types. The genus Cyphaspides is discussed, and an emended diagnosis is provided. The paleobiogeography, ontogeny, and relationships of the genus are discussed. UUID: http://zoobank.org/4a7aab8f-8c8e-4498-9cc2-6f8c69b85213